Influence of point-of-sale tobacco displays and plain black and white cigarette packaging and advertisements on adults: Evidence from a virtual store experimental study. (May 2016) - Nonnemaker, James; Kim, Annice; Shafer, Paul; Loomis, Brett; Hill, Edward; Holloway, John; Farrelly, Matthew
Abstract: Introduction: We examined the potential impact of banning tobacco displays and mandating plain packaging and cigarette advertisements at the point of sale (POS) on adult outcomes. Methods: A virtual convenience store was created with scenarios in which the tobacco product display was either fully visible (status quo) or enclosed behind a cabinet (display ban), and cigarette packs and advertisements were either in full color (status quo) or black and white, text only (plain). A national convenience sample of 1313 adult current smokers and recent quitters was randomized to 1 of 4 conditions and given a shopping task to complete in the virtual store. Main outcomes were participants' self-reported urge to smoke and tobacco purchase attempts in the virtual store. Results: Compared with recent quitters in the status quo conditions, recent quitters in the display ban condition had lower urges to smoke (β = − 4.82, 95% CI = − 8.16–− 1.49, p < 0.01). Compared with current smokers in the status quo conditions, smokers in the display ban conditions were less likely to attempt to purchase cigarettes in the virtual store (OR = 0.05, 95% CI = 0.03–0.08, P  < 0.01). Smokers exposed to plain packs and ads were significantly less likely to attempt to purchase cigarettes (OR = 0.31, 95% CI = 0.20–0.47, P  < 0.01) than those exposed to color packs and ads. Conclusions: Policies that ban the display of tobacco products or require plain packaging and advertising at the POS may help reduce adult smoking. Highlights: Smokers in the display ban conditions were less likely to attempt to purchase cigarettes. Smokers exposed to plain packs and ads were less likely to attempt to purchase cigarettes. Recent quitters in the display ban conditions reported lower urge to smoke. Enclosing the display had no significant influence on smokers' urge to smoke. Making the packs and ads plain had no significant influence on recent quitters' urge to smoke.